6(x+7)-2x=26

Simple and best practice solution for 6(x+7)-2x=26 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x+7)-2x=26 equation:


Simplifying
6(x + 7) + -2x = 26

Reorder the terms:
6(7 + x) + -2x = 26
(7 * 6 + x * 6) + -2x = 26
(42 + 6x) + -2x = 26

Combine like terms: 6x + -2x = 4x
42 + 4x = 26

Solving
42 + 4x = 26

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-42' to each side of the equation.
42 + -42 + 4x = 26 + -42

Combine like terms: 42 + -42 = 0
0 + 4x = 26 + -42
4x = 26 + -42

Combine like terms: 26 + -42 = -16
4x = -16

Divide each side by '4'.
x = -4

Simplifying
x = -4

See similar equations:

| (4+x)*(7+x)=72cm^2 | | x+7+5x=19 | | -3u+5(u-3)=1 | | 2h+3=17 | | 1x+(-1.2x)=27 | | 3(x+2)-2(2x-3)=13 | | -3x^2+6x+1=y | | 300-2P+4I=3P-50 | | (Y-3)2=4y-12 | | 18+6z=6 | | M-4m-m-5= | | -3x+6x+1=y | | 2x+4=x+60 | | 5x-6=6x-50 | | -4x(1-3)-(2x+2)=-4(5)(1-3)-(2(5)+2) | | -8+10k+2k=40 | | X-5+2x+9=50 | | 4(-8x+12)=-26-33x | | 13g+9-3f+2-12g= | | (k+4)= | | 2x+9+x-5=50 | | 4b-3-10b-4= | | 6x-4=(-2)x-10 | | 9=m-1+1 | | x^2+27x-124=0 | | 3d-5t+10+t+7d-6= | | 5a+2=5a | | 1.25=-4c+0.25 | | 6w*5w= | | 0.25+0.50t=4 | | 6-(-36)= | | -5(x+7)=4-(-2) |

Equations solver categories